Assessment of Strength and Bending of Concrete Containing Crushed Glass and Fibers - Firoozi, Ali Akbar; Firoozi, Ali Asghar; Dithinde, Mahongo; Bome, Obakeng (New Environmentally-Friendly Materials, 2024)
Abstract This paper presents proposed investigations of the influence of crushed glass and fibers on the mechanical properties of concrete. Conventional concrete has lack tension in order to improve its flexural strength and compressive strength. This study has adopted the addition of PET fibers and recycled waste glass fibers to concrete. The study uses M25 grade concrete to study the effects of adding crushed waste glass at a weight of 0, 5, 10, and 15%. The PET fibers were extracted from waste bottles used for packaging of drinks and hand cut into very small rectangular pieces (with an average size of 3×10mm). For the mix design, the addition of 0, 3, 5, and 10% dosages of PET fiber was adopted to compare their influence against plain concrete with no fiber addition. Both fiber samples were tested for compressive strength and flexural strength and samples were cured for 7, 28, 56, and 90 days. Results showed that the combination of using crushed glass and PET fibers has a significant effect on compressive strength (i.e., 122%) and flexural beam test (56%) for 90 days of cured samples.